A 24-month National Cohort Study examining long-term effects of COVID-19 in children and young people - Terence Stephenson; Snehal M. Pinto Pereira; Manjula D. Nugawela; Emma Dalrymple; Anthony Harnden; Elizabeth Whittaker; Isobel Heyman; Tamsin Ford; Terry Segal; Trudie Chalder; Shamez N. Ladhani; Kelsey McOwat; et al. (Communications Medicine)
Abstract Background Some children and young people (CYP) infected with SARS-COV-2 experience impairing symptoms post-infection, known as post-COVID-19 condition (PCC). Using data from the National Long COVID in Children and Young People (CloCk) study, we report symptoms and their impact up to 24-months post-infection. Methods CloCk is a cohort of CYP in England aged 11-to-17-years when they had a SARS-CoV-2 PCR-test (between September 2020 and March 2021). Of 31,012 eligible CYP 24-months post-PCR test, 12,632 participated (response = 40.7%). CYP were grouped by infection status: ‘initial test-negatives; no subsequent positive-test’ (NN); ‘initial test-negatives; subsequent positive-test’ (NP); ‘initial test-positives; no reported re-infection’ (PN); and ‘initial test-positives; reported re-infection’ (PP). The Delphi research definition of PCC in CYP was operationalised; symptom severity/impact and validated scales (e.g., Chalder Fatigue Scale) were recorded. We examine symptom profiles 24-month post-index-test by infection status. Results 7.2% of CYP consistently fulfil the PCC definition at 3-, 6-, 12- and 24-months. These CYPs have a median of 5-to-6 symptoms at each time-point. Between 20% and 25% of all infection status groups report 3+ symptoms 24-months post-testing; 10–25% experience 5+ symptoms. The reinfected group has more symptoms than the other positive groups; the NN group has the lowest symptom burden (p < 0.001). PCC is more common in older CYPs and in the most deprived. Symptom severity/impact is higher in those fulfilling the PCC definition. Conclusions The discrepancy in the proportion of CYP fulfilling the Delphi PCC definition at 24-months and those consistently fulfilling the definition across time, highlights the importance of longitudinal studies and the need to consider clinical impairment and range of symptoms.